Pengaruh Kinerja Karyawan Terhadap Kepercayaan Nasabah Pada PT. GROUP LEASE FINANCE INDONESIA ( Pos Turikale ) Kabupaten Maros. - Asy'ari, Abu Hasan; Yakub, Yakub (Jurnal Metaverse ADPERTISI, 2023)
This study aims to determine the effect of employee performance with indicators (quality of work, quantity of work, responsibility, cooperation, initiative) significantly affect customer trust. using simple linear regression analysis and hypothesis testing by giving questionnaires to customers, then quantitative methods using Likert scale analysis to measure each indicator of employee performance. The results of this study indicate that employee performance has a positive and significant effect on customer trust. The results above show that the hypothesis proposed by the research is accepted.